Treatment of wastewater containing mineral oil by sorption onto granulated cork - Ferreira, Catarina Isabel de Almeida (2014)
The aim of this work is the development of a new method to remove oils from wastewaters, namely hydrocarbons. These contaminants, when present in high concentrations, are efficiently removed by physical and chemical processes, such as gravity separators, flocculation and flotation processes; however for low concentrations, these methods are not applicable [1]. Moreover, advanced separation processes such as membrane separation [2] and activated carbon adsorption [3] are expensive options for the treatment of oil-containing wastewaters. This new technique is based on oil and hydrocarbons’ sorption on cork granules.